2004
DOI: 10.1126/science.1100569
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Dpr2 Inhibits Mesoderm Induction by Promoting Degradation of Nodal Receptors

Abstract: Nodal proteins, members of the transforming growth factor-beta (TGFbeta) superfamily, have been identified as key endogenous mesoderm inducers in vertebrates. Precise control of Nodal signaling is essential for normal development of embryos. Here, we report that zebrafish dapper2 (dpr2) is expressed in mesoderm precursors during early embryogenesis and is positively regulated by Nodal signals. In vivo functional studies in zebrafish suggest that Dpr2 suppresses mesoderm induction activities of Nodal signaling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
166
3
13

Year Published

2005
2005
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 124 publications
(189 citation statements)
references
References 23 publications
7
166
3
13
Order By: Relevance
“…Although I found that ␤-catenin, Sqt, and Boz could induce ectopic dpr1 and dpr2 expression, only ␤-catenin signaling was required for their initiation. In contrast to what has been reported by Zhang et al (2004), Nodal signaling was only required for maintenance of mesodermal dpr1 and dpr2 expression in the margin during gastrulation. I also found that inhibition of the ventralizing signal bone morphogenetic protein (BMP) by the BMP-antagonist Noggin led to ectopic expression of dpr1 and dpr2.…”
Section: Introductioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Although I found that ␤-catenin, Sqt, and Boz could induce ectopic dpr1 and dpr2 expression, only ␤-catenin signaling was required for their initiation. In contrast to what has been reported by Zhang et al (2004), Nodal signaling was only required for maintenance of mesodermal dpr1 and dpr2 expression in the margin during gastrulation. I also found that inhibition of the ventralizing signal bone morphogenetic protein (BMP) by the BMP-antagonist Noggin led to ectopic expression of dpr1 and dpr2.…”
Section: Introductioncontrasting
confidence: 99%
“…Both dpr1 and dpr2 are expressed on the prospective dorsal side of the embryo shortly after the initiation of zygotic transcription (Zhang, 2004;Waxman et al, 2004). In contrast to what is observed in Xenopus, we have found that Dpr1 is not required for organizer formation but rather aids Wnt8 promotion of ventroposterior patterning (Waxman et al, 2004).…”
Section: Introductioncontrasting
confidence: 81%
See 3 more Smart Citations